Anatomical and histological changes of uterine horn of Aceh cattle with repeat breeding - Thasmi, Cut Nila; Siregar, Tongku Nizwan; Wahyuni, Sri; Aliza, Dwinna; Panjaitan, Budianto; Nazaruddin, Nazaruddin; Sabila, Firschilia Nurul; Fallatanza, Miranda (Journal of Advanced Veterinary and Animal Research, 2018)
Objective: This study aimed to observe the changes in anatomical pathology, histopathology, and histomorphometry of uterine horn in Aceh cattle with repeat breeding (RB). Materials and methods: In this study, five uterine horns were collected from fertile Aceh cattle (N1, N2, N3, N4, and N5) and Aceh cattle with RB (RB1, RB2, RB3, RB4, and RB5). Changes in the anatomical pathology of uterine horn were observed prior to histopathological preparations. The results were analyzed descriptively. Results: The observation of anatomical pathology revealed that the uterus of fertile cattle was yellowish white with horn-like shape consisting of hollow muscles, while RB cattle were reddish-pale. Furthermore, uterine horn swelling with purulent exudate was observed in the uterine horn of RB1 and RB4, while swelling with serous exudates was found in RB2, RB3, and RB5. Thin-walled uterine horn with caruncular atrophy was observed only in RB3. Histopathological observations showed erosion and hyperplasia of endometrial columnar epithelial and uterine glands in RB1, RB2, RB4, and RB5. Atrophy of uterine gland was found in RB3 and edema of caruncular was observed in RB1 and RB4. In addition, hemorrhage and inflammatory cell infiltration (neutrophils, lymphocytes, and macrophages) were found in all RB cattle. Histologically, cow uterus is divided into three layers, endometrium, myometrium, and perimetrium with the uterine gland found in the endometrium. Histomorphometric measurements found that the uterine horn wall (endometrial, myometrial, and perimetrium) of RB cattle were thicker than of fertile Aceh cattle, 208.06 ± 39.90 vs. 187.39 ± 29.09 μm, 400.138 ± 51.96 vs. 277.91 ± 42.88 μm, and 23.59 ± 9.67 vs. 18.53 ± 4.40 μm. However, the endometrial gland diameter of RB cattle is smaller than that of fertile Aceh cattle, 4.04 ± 0.88 vs. 4.99 ± 1.37 μm. Conclusion: The changes in anatomical pathology and histopathology of the uterine horn of Aceh cattle with RB indicate endometritis which caused by subacute and chronic bacterial infections. Endometritis causes disrupted blood circulation, which is characterized by hemorrhage, edema, and thickening of the endometrium, myometrium, and perimetrium, resulting in an increased diameter of the endometrial gland in RB Aceh cattle. http://doi.org/10.5455/javar.2018.e297